The immune escape in melanoma: role of the impaired dendritic cell function. (October 2014) - Tucci, Marco; Stucci, Stefania; Passarelli, Anna; Giudice, Giuseppe; Dammacco, Franco; Silvestris, Franco
Abstract : Melanoma is an immunogenic cancer that overcomes the control of the immune system through the production of tolerogenic cytokines and growth factors in the microenvironment. In melanoma, dendritic cells (DC) show severe alterations in maturation, cross-priming and antigenic presentation, while other accessory cells infiltrating the tumor milieu also suppress DCs through the activation of the STAT pathway by IL-10 and IL-6. Novel immunotherapy strategies blocking cytotoxic T-lymphocyte antigen (CTLA-4) are successful in advanced disease, while melanoma cells carrying the BRAF V600E mutation further reinforce the immune suppression by activating MAPKs. Here, we review the major mechanisms involved in the cross-talk between melanoma cells and the immune system as well as the issue of defects in DCs in relation to novel studies aimed at restoring their anti-tumor activity.